Response of physiological characteristics of ecological restoration plants to substrate cement content under exogenous arbuscular mycorrhizal fungal inoculation - Shu, Qian; Xia, Dong; Ma, Yueyang; Zhang, Yang; Luo, Ting; Ma, Jiaxin; Liu, Fang; Yan, Shuxing; Liu, Daxiang (Frontiers in Plant Science, 2022)
Introduction In order to solve the inhibition of alkaline environment on plants growth at the initial stage of Eco-restoration of vegetation concrete technology, introducing AMF into vegetation concrete substrate is an effective solution. Methods In this study, Glomus mosseae (GM), Glomus intraradices (GI) and a mixture of two AMF (MI) were used as exogenous inoculation agents. Festuca elata and Cassia glauca were selected as host plants to explore the relationship between the physiological characteristics of plants and the content of substrate cement under exogenous inoculation of AMF. Results The experiment showed that, for festuca elata, the maximum mycorrhizal infection rates of inoculation with GM, MI were when the cement contents ranged 5–8% and that of GI inoculation was with the cement contents ranging 5–10%. Adversely, for Cassia glauca, substrate cement content had little effect on the root system with the exogenous inoculation of AMF. Compared with CK, the effects of AMF inoculation on the physiological characteristics of the two plants were different. When the cement content was the highest (10% and 8% respectively), AMF could significantly increase(p<0.05) the intercellular CO2 concentration (Ci) of Festuca elata. Moreover, for both plants, single inoculation was more effective than mixed inoculation. When the cement content was relatively low, the physiological characteristics of Cassia glauca were promoted more obviously by the inoculation of GI. At higher cement content level, inoculation of GM had a better effect on the physiological characteristics of the two plants. Conclusion The results suggest that single inoculation of GM should be selected to promote the growth of Festuca elata and Cassia glauca in higher alkaline environment.